Bank Consolidation, Internationalization, and Conglomeration : Trends and Implications for Financial Risk - De Nicolo, Gianni (IMF Working Papers; Working Paper, 2003)
This paper documents global trends in bank activity, consolidation, internationalization, and financial firm conglomeration, and explores the extent to which financial firm risk and systemic risk potential in banking are related to consolidation and conglomeration. We find that while there is a substantial upward trend in conglomeration globally, consolidation and internationalization exhibit uneven patterns across world regions. Trends in consolidation and conglomeration indicate increased risk profiles for large, conglomerate financial firms, and higher levels of systemic risk potential for more concentrated banking systems. We outline research directions aimed at explaining why bank consolidation and conglomeration do not necessarily yield either safer financial firms or more resilient banking systems.